Generation of reactive species in water film dielectric barrier discharges sustained in argon, helium, air, oxygen and nitrogen. (3rd August 2020) - Mohades, Soheila; Lietz, Amanda M; Kushner, Mark J
Abstract: Activation of liquids with atmospheric pressure plasmas is being investigated for environmental and biomedical applications. When activating the liquid using gas plasma produced species (as opposed to plasmas sustained in the liquid), a rate limiting step is transport of these species into the liquid. To first order, the efficiency of activating the liquid is improved by increasing the ratio of the surface area of the water in contact with the plasma compared to its volume—often called the surface-to-volume ratio (SVR). Maximizing the SVR then motivates the plasma treatment of thin films of liquids. In this paper, results are discussed from a computational investigation using a global model of atmospheric pressure plasma treatment of thin water films by a dielectric barrier discharge (DBD) sustained in different gases (Ar, He, air, N2, O2 ). The densities of reactive species in the plasma activated water (PAW) are evaluated. The residence time of the water in contact with the plasma is increased by recirculating the PAW in plasma reactor. Longer lived species such as H2 O2aq and NO3 − aq accumulate over time (aq denotes an aqueous species). DBDs sustained in Ar and He are the most efficient at producing H2 O2aq, DBDs sustained in argon produces the largest density of NO3 − aq with the lowest pH, and discharges sustained in O2 and air produce the highest densities of O3aq . Comparisons to experiments by others show agreement in the trends in densities in PAW including O3aq, OHaq, H2 O2aq and NO3 − aq, and highlight the importance of controlling desolvation of species from the activated water.